MODEL PROBLEM BASED LEARNING BERBASIS GAMIFIKASI PENGARUHNYA TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Ninis Nur Cahyanti; Sri Sumaryati (Jurnal Pengembangan Pendidikan Akuntansi dan Keuangan (JPPAK), 2025)
This study aimed to analyze the effect of the gamification-based Problem Based Learning (PBL) model on students' critical thinking skills in commercial accounting learning. The approach used in this research was a quasi-experimental design with a nonequivalent control group design. The research sub jects consisted of two 11th grade Financial Accounting (AKL) classes at a vocational school in Surakar ta, which were selected using simple random sampling. The results of the data analysis showed that the application of the gamification-based PBL model had a significant effect on improving students' critical thinking skills. This was supported by the independent sample t-test with a significance value of 0.010 and the paired sample t-test with a significance value of 0.000, both of which were less than 0.05. In ad dition, the N-Gain value indicated an improvement in students' critical thinking skills in the moderate category.Keywords: Critical Thinking Skills; Gamification; Problem Based Learning